2012
DOI: 10.1063/1.4756907
|View full text |Cite|
|
Sign up to set email alerts
|

Performance of p- and n-side illuminated microcrystalline silicon solar cells following 2 MeV electron bombardment

Abstract: The impact of defects on the performance of p- and n-side illuminated microcrystalline silicon solar cells is investigated. The absorber layer spin density NS is controlled over some two orders of magnitude by electron bombardment and subsequent annealing steps. At increased NS (between 3 × 1016 and 1018 cm−3), performance of n-side illuminated cells is much more strongly reduced relative to p-side illuminated cells, particularly with regard to short circuit current density. Quantum efficiency measurements ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The electron bombardment creates defects in every layer of the solar cell stack including glass substrate. Nevertheless, we expect that the photovoltaic performance is predominantly determined by the increase in the defect density of absorber layer rather than other functional layers of a cell [9][10][11].…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…The electron bombardment creates defects in every layer of the solar cell stack including glass substrate. Nevertheless, we expect that the photovoltaic performance is predominantly determined by the increase in the defect density of absorber layer rather than other functional layers of a cell [9][10][11].…”
Section: Methodsmentioning
confidence: 98%
“…Both the solar cells and ESR samples underwent identical 2 MeV electron bombardment with fluence of 9.4 × 10 16 e/cm 2 at approximately 100 K, and subsequent stepwise annealing as described in our previous publications [8][9][10][11]16]. In the following discussion the spin density, N S , measured in the reference samples, is referred to as the defect density in the absorber layer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the hole drift mobility and mobilitylifetime product in c-Si:H films are much higher than those in a-Si:H films [3]. It was recently shown that the performance of p-side and n-side illuminated solar cells with microcrystalline silicon absorber layers is quite similar provided that the defect density of the absorber layer is sufficiently low [4]. High efficiency c-Si:H solar cells with illumination from the n-side have been demonstrated with highly transparent n-type alloys as window layers, for example, silicon carbide [5] or microcrystalline silicon oxide (c-SiO x :H) [6].…”
Section: Introductionmentioning
confidence: 97%